Efforts to Increase the Income of Seaweed Farming Woman Group in Kutuh Village Through Digital Marketing - Adie Wahyudi Oktavia Gama; Nimadeni Yuniartika; Gusi Putu Lestara Permana (Institut Teknologi Nasional, Bandung, 2023)
Kutuh Village is a village located in the southern Bali area which is the main seaweed production in Bali. The women in this area have started to become entrepreneurs by forming the Seaweed Woman Farmers Group (SWF) and until now they have continued to process seaweed. However, they have had problems in marketing seaweed products more broadly because so far they have only depended on orders from distributors. This community service program was carried out to provide simple management assistance by utilizing current technology, known as digital marketing as a way to increase business income for woman farmer groups. Through this activity the results that have been achieved are an increase in buyers within and outside the Kutuh Village area to buy seaweed products directly or online, so that products from processed seaweed are increasingly widespread in terms of marketing in the digital era as it is today.